General trends in world biogeographic literature: a preliminary bibliometric analysis - Morrone,Juan J. (2008)
Records with the search string biogeograph* were collected from the Science Citation Index (SCI). A total of 3456 records were downloaded for the 1945-2006 period from titles of articles and reviews, and 10,543 records were downloaded for 1991-2006, taking into consideration also abstracts and keywords. Temporal trends of publications, geographical and institutional distribution of the research output, authorship, and core journals were evaluated. There were as many as 122 countries carrying out biogeographic research; in the most recent period, USA is the top producing country, followed by the United Kingdom, Australia, France, Germany, Spain, and Canada. There were 17,493 authors contributing to the field. During 1991-2006 there were 4098 organizations with authors involved in biogeographic research; institutions with higher number of papers are the Natural History Museum (United Kingdom), the University of California, Berkeley (USA), the Museum National d'Histoire Naturelle (France), the Universidad Nacional Autónoma de México (Mexico), the American Museum of Natural History (USA) and the Russian Academy of Sciences (Russia). Research articles are spread over a variety of journals, with the Journal of Biogeography, Molecular Phylogenetics and Evolution, Molecular Ecology, and Biological Journal of the Linnean Society being the core journals. From 28,759 keywords retrieved those with the highest frequency were evolution, phylogeny, diversity, mitochondrial DNA, pattern(s), systematics, and population(s). We conclude that publications on biogeography have increased substantially during the last years, especially since 1998. The preferred journal for biogeographic papers is the Journal of Biogeography. Most frequent keywords seem to indicate that biogeography fits well within both evolutionary biology and ecology, with molecular biology and phylogenetics being important factors that drive their current development.